Keefektifan Pemberian Informasi Karier melalui Narasumber untuk Meningkatkan Taraf Kematangan Karier Siswa SMA - Abdullah Abdullah (Ilmu Pendidikan: Jurnal Kajian Teori dan Praktik Kependidikan, 2007)
This study is aimed at examining the effectiveness of using professionals in giving career information to increase the high school students' career maturity level. The study was an experimental in nature using 60 samples. In the experimental group the career information was delivered by professionals who were successful in their careers, while in the control group the information was given through the packet book (conventional technique).The sampling technique used was the multi-stage random. The instrument employed was the Career Maturity Scale. The data analysis was done using statistical t-test. The result indicates that the career information delivered by professionals is more effective than given through packet book.